Biosecurity Levels Related to Transmission of Highly Pathogenic Avian Influenza (HPAI) in Live Bird Markets in Bogor - Miftahurridho, Zoelva; Purnawarman, Trioso; Basri, Chaerul (Jurnal Sain Veteriner, 2026)
Live bird markets serve as aggregation points for various types of poultry originating from different geographic areas. That condition makes live bird market as a potential hotspot for disease transmission. High levels of human and live poultry movement, low awareness of hygiene and sanitation, and inadequate implementation of biosecurity practices can substantially increase the risk of disease transmission in live bird market. This study aimed to evaluate the implementation level of biosecurity among traders in live bird markets in Bogor City and Bogor Regency. A total of 15 traders were selected and assessed using a checklist adapted from Biosecurity Guide for Live Poultry Markets published by Food and Agriculture Organization (FAO). The assessment focused on three main components of biosecurity: movement control, isolation, and sanitation. Biosecurity levels were categorized as good, moderate, and poor level based on result from assessment. The result showed that biosecurity level among traders in live bird markets was moderate (100%). However, a relatively high degree of non-compliant was still observed across all biosecurity components. Therefore, improvements in biosecurity implementation are necessary, both through enhancing traders’ knowledge and awareness, improving market management by market authorities, and establishing clear and enforceable regulations by government.